Pre-operative hepatic artery resistive index is a non-invasive predictive indicator of prognosis in biliary atresia - Deepak Mittal; Veereshwar Bhatnagar; Sandeep Agarwala; Maddur Srinivas; Manisha Jana; Arun Kumar Gupta; Nibhriti Das; Manoj Kumar Singh (Wolters Kluwer Medknow Publications, 2017)
Aims: The aim of this study is to evaluate hepatic artery resistive index (HARI) as a noninvasive prognostic predictor by correlating it with peripheral blood nitric oxide (NO) levels, portal pressure (PP) and histopathological changes in the liver in patients of biliary atresia (BA). Materials and Methods: Twenty-five patients were included in the study prospectively from November 2012 to June 2014. All patients underwent Doppler sonography to calculate the HARI preoperatively. Peripheral blood NO was also measured preoperatively. Biochemical liver function tests (LFTs) were measured preoperatively and at 1, 3, and 6 months postoperatively. The PP was measured intraoperatively, and a liver biopsy was taken in all patients. Disappearance of jaundice defined successful surgical treatment. Postoperatively, a hepatobiliary IminoDiacetic Acid scan (HIDA) was done to demonstrate a patent bilio-enteric pathway. Results: The mean preoperative HARI was 0.78 ± 0.105, and the median was 0.80 (range 0.60-1.0). The median HARI was used to correlate the other parameters; 13 (52%) patients had HARI ≥0.8. The mean PP was 24.96 ± 6.54 mmHg. The HARI had a strong correlation with PP (P = 0.0001) and (NO) (P = 0.0001); with every 0.1 increase in HARI, there was 5.2 mmHg increase in PP and 3.8 μmol/L increase in NO. The histological parameters which reached significance in relation to HARI were hepatocellular damage, bile duct inflammation, portal inflammation, and portal fibrosis. The postoperative improvement in LFT was significantly better in patients with HARI <0.8. All four patients who died during or after the study period had HARI >0.8, elevated PP, and NO levels. Conclusions: Preoperative HARI was found to have a direct correlation with PP and peripheral blood NO as a measure of portal hypertension. A preoperative HARI ≥0.8 should be considered as a risk factor for poor outcomes in BA.